Cuando las ilustraciones cobran protagonismo : las propuestas gráficas de Ayax Barnes en libros infantiles (1966-1976) - Krause, Flavia M. J. (2024)
The aim of this study is to explore the work of Ayax Barnes (1926-1996), one of the main illustrators for children in Argentina, from 1966 to 1976. We start from the assumption that there is a relationship between the graphic proposals in children's books and the representations of childhood. We postulate that, depending on how Barnes' illustrations intertwine with the texts in the books, it is possible to locate them in a passage from illustrated book to picture book and modern design. And in turn, this distribution of materials for children corresponds to different representations of childhood.\nWe consider the international context is embedded in the national context. On the other hand, we chose for this thesis to study Barnes' proposals from a multidisciplinary perspective of analysis that dialogues with semiotics, art, design and children's picture book studies. \nThis artist's work is the epitome of the way in which graphic proposals modified their place and function in books and, at the same time, how this prominence of graphic language was linked to changes in the representations of childhood in the period between dictatorships.